Policies for youth employment in Sub-Saharan Africa - Schwebel, David; Estruch, Elisenda; Wobst, Peter; Grandelis, Ileana (International Food Policy Research Institute, 2019)
Chapter 3 reviews national policies in 13 African countries, and uses a novel approach to classify policies according to the employment constraints they address. One reason for the attention given to job creation is the belief that unemployed youth are a potential source of political instability and unrest.